VD_FINDINFO MP / 2023 / 2 vom 1. Januar 2021 - VD Tribunal cantonal (2021)
IMITATIONPROPRIÉTÉ INTELLECTUELLE, CONCURRENCE DÉLOYALE | 2 LCD, 3 al. 1 let. a LCD, 3 al. 1 let. b LCD, 3 al. 1 let. d LCD, 3 al. 1 let. e LCD, 5 let. a LCD, 5 let. b LCD, 5 let. c LCD, 6 LCD, 10 LDIP, 109 al. 1 LDIP, 109 al. 2 LDIP, 110 al. 1 LDIP, 264 CPC (CH), 267 CPC (CH), 36 CPC (CH), 99 CPC (CH)